2012
DOI: 10.1128/aac.00052-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blaZ Gene Types and the Inoculum Effect with Cefazolin among Bloodstream Isolates of Methicillin-Susceptible Staphylococcus aureus

Abstract: ABSTRACTWe sought to define the prevalence ofblaZgene types and the inoculum effect to cefazolin among methicillin-susceptibleStaphylococcus aureus(MSSA) bloodstream infections. TheblaZgene was present in 142/185 (77%) isolates. A total of 50 (27%) isolates had a ≥4-fold increase in the cefazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
2
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 24 publications
4
54
2
3
Order By: Relevance
“…Additionally, our cohort included 32 (31.1%) cefazolin-treated and 20 (34.5%) oxacillin-treated patients with overall deep-seated infections, also resulting in similarly common in-hospital treatment failure rates, at 15.6% (5/32) for cefazolin and 20% (4/20) for oxacillin. Higher failure rates with cefazolin as a result of overproduction of certain types of ␤-lactamases in deep-seated infections have been reported (14,15). However, neither cefazolin nor oxacillin in our study was independently associated with treatment failure, even with the presence of deepseated infections.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Additionally, our cohort included 32 (31.1%) cefazolin-treated and 20 (34.5%) oxacillin-treated patients with overall deep-seated infections, also resulting in similarly common in-hospital treatment failure rates, at 15.6% (5/32) for cefazolin and 20% (4/20) for oxacillin. Higher failure rates with cefazolin as a result of overproduction of certain types of ␤-lactamases in deep-seated infections have been reported (14,15). However, neither cefazolin nor oxacillin in our study was independently associated with treatment failure, even with the presence of deepseated infections.…”
Section: Discussioncontrasting
confidence: 55%
“…However, deepseated infections with a high burden of S. aureus have been shown to overproduce certain types of ␤-lactamases, rendering cefazolin inactive and thus resulting in possible treatment failure (13)(14)(15). Furthermore, current practice guidelines, such as those for infective endocarditis, suggest reserving the use of cefazolin for patients with nonanaphylactoid-type penicillin allergies (7).…”
mentioning
confidence: 99%
“…The efficacy of CFZ in vivo was restored when the strain was cured of ␤-lactamase (TX0117c) (21). The results of the current work reiterate that the CFZ InE can influence the efficacy of CFZ in vivo (4,5). While the percentage of MSSA infections in which the InE may have a clinical effect appears to be quite small, it nonetheless is of concern when the inoculum is large, such as a large vegetation or an undrained abscess.…”
Section: Discussionmentioning
confidence: 61%
“…There are published reports (including from our group) that correlate the CFZ inoculum effect with clinical failure (4,5,7,14,16). These reports have shown that, in the majority of the strains, an increase in the CFZ MICs (tested at high inoculum) was associated with the presence of type A ␤-lactamase (4, 5, 7).…”
Section: Discussionmentioning
confidence: 91%
“…Type A beta-lactamases, in particular, have been hypothesized to contribute to cefazolin treatment failure since they efficiently hydrolyze cefazolin. These reports have demonstrated an increase in MICs for high inocula of MSSA isolates that produce type A beta-lactamases (6,7). However, only isolated case reports have described clinical failures with cefazolin therapy for MSSA endocarditis, and the clinical relevance of this in vitro phenomenon is unclear.…”
mentioning
confidence: 96%